Sosialisasi dalam Keluarga Terhadap Pembentukan Akhlak Anak - Hidayatun Ni’mah; Abdul Hadi; Muhammad Hambal Shafwan (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
Socialization is a process in which a person gets new things from other people. This new thing can be in the form of knowledge or experience. This is how this concept is defined generally within the scope of sociological studies. Each individual's socialization environment is different. Starting from the smallest environment, such as family, close friends, then to the wider community and even worldwide. A person's personality can be formed after receiving what is given within their scope or environment as a function of socialization. A child's personality or morals can easily be obtained from the family environment. How to socialize in the family so that good morals are formed for children. One way is to teach good religious and social norms, apart from that, the most important thing is to provide a good role model or example. This research uses a qualitative descriptive method, namely field study. Researchers process data from the field using a qualitative approach, where the data obtained is the result of the researcher's observations. The research results show that among the many factors that influence the formation of children's morals, family socialization is the main factor for the formation of children's morals. Because family is the closest small group.